Handling Selection of Settlement and Embankment Stability Issues Based on Variations in Embankment Height and Soft Subgrade Thickness Case Study: Pekanbaru Junction - Pekanbaru Bypass Sta. 176+775 - Sta. 176+975 - Pandu Hermawan; Noor Endah Mochtar; Indrasurya B. Mochtar; Mahar Muliawan (Departemen Teknik Sipil, Institut Teknologi Sepuluh Nopember, 2025)
Trans Sumatra Toll Road (JTTS) is one of the most important infrastructure projects in Indonesia. One of the main sections of JTTS is the Rengat - Pekanbaru Toll Road, Pekanbaru Ring Section (Pekanbaru Junction - Pekanbaru Bypass). Existing conditions at Sta 176+775 - Sta 176+975 are dominated by oil palm plantations with soft soil layers in the form of organic soil to a depth of 1.0 meter; the layer below is clay with medium to stiff consistency. The existing treatment plan is preloading embankment with PVD and 1,0 m deep subgrade replacement. In this study, alternative planning calculations were carried out with variations of subgrade replacement up to 0.5 m and 1,0 m thickness. The study results show that the most cost-optimal treatment design is the treatment design without replacement with geotextile reinforcement. The thicker the subgrade replacement, the smaller the compression and rate of settlement. In terms of embankment reinforcement, the thicker the subgrade replacement, the less reinforcement is required. The thickness of subgrade replacement also affects the cost of the work, the thicker the subgrade replacement, the higher the cost of the work.